Investigation of The Secondary Structure and Interaction of hPin1 with Cobalt Ion by Fourier Transform Infrared Spectroscopy - Lin, Tao; Wang, Jingzhang; Li, Lingjin; Du, Linfang (Asian Journal of Chemistry, 2010)
The secondary structure and stability of Pin1 in present of Co2+ ion were characterized in solution using Fourier transform infrared (FTIR) spectroscopy. Spectra and its derivation, selfdeconvolution and curve-fitting methods were used to analyze the secondary structure of hPin1. Composite bands of the amide I and amide III were studied by using Fourier self-deconvolution with an enhancement factor of K = 1.8 and a half width of 19.8 cm-1. Quantative analyses of the amide I band (1700-1600 cm-1) showed that native hPin1 contains 19 % α-helix, 33 % β-sheet, 12 % turn and 23 % disorder structures. In the presence of 1 equiv of Co2+, the hPin1 contains 26 % α-helix, 60 % β-sheet, 4 % turn and 4 % disorder structures. These results indicate that conformational changes in hPin1 take place when Co2+ bound.